A Comprehensive Systematic Review of The Relationship between Uncontrolled Hypertension and the Incidence of Vascular Dementia - Andi Riska Gunawati; Tika W. Rahajaan (International Medical Journal Corp. Ltd, 2026)
Introduction: Hypertension is a highly prevalent modifiable risk factor for dementia, yet the specific relationship between uncontrolled hypertension and vascular dementia remains incompletely characterized. This systematic review aims to synthesize current evidence on the association between uncontrolled hypertension and vascular dementia incidence, examining the effects of blood pressure control, treatment duration, and age-dependent factors. Methods: A systematic literature search was conducted following PRISMA guidelines. Studies were included if they examined adult patients (≥18 years) with diagnosed hypertension, clearly defined uncontrolled hypertension as an exposure variable, assessed vascular dementia as a primary or secondary outcome, and provided analyzable data. Observational studies (cohort, case-control, cross-sectional), systematic reviews, and meta-analyses were eligible. Data extraction encompassed study characteristics, hypertension definitions, dementia outcomes, association findings, confounders, and quality indicators. Results: One hundred twenty-five studies met inclusion criteria, encompassing over 2.6 million participants across diverse geographic settings. Uncontrolled hypertension was consistently associated with increased vascular dementia risk, with incidence rates of 8.1 versus 4.9 per 1,000 person-years in uncontrolled versus controlled groups (p<0.001). Antihypertensive treatment reduced dementia risk by 7-13% (OR 0.87-0.93), with each additional treatment year conferring 5-6% risk reduction. Midlife hypertension (ages 40-65) increased dementia risk by 63% (HR 1.63, 95% CI 1.37-1.89), whereas associations in late life were heterogeneous. Blood pressure variability independently predicted dementia (HR 1.69, 95% CI 1.25-2.28). Vascular markers including white matter hyperintensities, cerebral microbleeds, and microinfarcts mediated these relationships. Discussion: The hypertension-dementia relationship exhibits pronounced age dependence, with midlife exposure showing strongest associations through cumulative cerebrovascular damage. Blood pressure control effectiveness varies by dementia subtype, with stronger effects for vascular than Alzheimer's dementia. Treatment duration, blood pressure variability, and multifactorial risk factor control represent critical modifiers of cognitive outcomes. Conclusion: Uncontrolled hypertension significantly increases vascular dementia risk, with optimal blood pressure control in midlife offering substantial cognitive protection. Future research should address ethnic diversity, optimize late-life blood pressure targets, and evaluate combination risk factor interventions.